Genomic relationships between the cultivated peanut (Arachis hypogaea, Leguminosae) and its close relatives revealed by double GISH - Seijo, José Guillermo (2007)
Arachis hypogaea is a natural, well-established allotetraploid (AABB) with 2n = 40. However, researchers disagree on the diploid genome donor species and on whether peanut originated by a single or multiple events of polyploidization. Here we provide evidence on the genetic origin of peanut and on the involved wild relatives using double GISH (genomic in situ hybridization). Seven wild diploid species (2n=20), harboring either the A or B genome, were tested. Of all genomic DNA probe combinations assayed, A. duranensis (A genome) and A. ipaensis (B genome) appeared to be the best candidates for the genome donors because they yielded the most intense and uniform hybridization pattern when tested against the corresponding chromosome subsets of A. hypogaea. A similar GISH pattern was observed for all varieties of the cultigen and also for A. monticola. These results suggest that all presently known subspecies and varieties of A. hypogaea have arisen from a unique allotetraploid plant population, or alternatively, from different allotetraploid populations that originated from the same two diploid species. Furthermore, the bulk of the data demonstrated a close genomic relationship between both tetraploids and strongly supports the hypothesis that A. monticola is the immediate wild antecessor of A. hypogaea.